PENGARUH METODE WRITING IN THE HERE AND NOW TERHADAP KEMAMPUAN MENULIS CERPEN KELAS X SMK SWASTA TERUNA PADANGSIDIMPUAN - Harahap, Nurjanna; Daulay, Ismail Rahmad; Aritonang, Devinna Riskiana (Universitas Muhammadiyah Tapanuli Selatan, 2024)
Abstract Â This study aims to: (1) Know the use of the Writing in The Here and Now method for class X students of the Padangsidimpuan Teruna Private Vocational School. (2) Knowing the ability to write short stories in class X students of the Padangsidimpuan Teruna Private Vocational School (3) Knowing the effect of using the Writing in The Here and Now method on the ability to write short stories in class X students of Padangsidimpuan Teruna Private Vocational School. This research is a type of quantitative research in the form of numbers and scores. The method used in this research with a quantitative. The student population is 285 students, 254 male students and 31 female students. The sample in this study was Software Engineering class X, the sample subjects were 25 students. The sample collection make Simple Random Sampling. Data collection used are questionnaires and tests. The average value on the X variable is 75.60 in the